Effectiveness of Mental Health First Aid: a meta-analysis. Issue 4 (28th November 2019) - Maslowski, Amy K.; LaCaille, Rick A.; LaCaille, Lara J.; Reich, Catherine M.; Klingner, Jill
Abstract : Purpose: The purpose of this paper, a meta-analysis and systematic review of Mental Health First Aid (MHFA), is to focus on studies that reported trainees' mental health literacy, attitudes and helping-related behaviors, as well as the impact of the program for the people who came into contact with trainees (i.e. recipients). Design/methodology/approach: A systematic search included several online databases of published studies, dissertations or theses, and journals commonly publishing research in this area. Studies were randomized or non-randomized control trials using an intervention based upon the adult or youth MHFA curriculum. Findings: Of the 8, 257 initial articles, 16 met inclusion criteria. Small-to-moderate effect sizes (Hedges' g =0.18–0.53) were found for the primary outcomes for the trainees with effects appearing to be maintained at follow-up. Study quality was inversely associated with effect size. No evidence of investigator allegiance was detected. Few studies examined the effects for those who received aid from a MHFA trainee. Preliminary quantitative evidence appeared lacking (Hedges' g =−0.04 to 0.12); furthermore, a qualitative review found limited positive effects. Research limitations/implications: MHFA trainees appear to benefit from MHFA; however, objective behavioral changes are in need of greater emphasis. Additionally, considerably greater attention and effort in testing effects on distressed recipients is needed with future empirical investigations. Originality/value: This is the first known review that includes preliminary findings on the effects of MHFA on the distressed recipients of the aid. It is anticipated that this will prompt further investigation into the impact of MHFA.